2016
DOI: 10.1080/09540121.2016.1178954
|View full text |Cite
|
Sign up to set email alerts
|

Access for all: contextualising HIV treatment as prevention in Swaziland

Abstract: This article explores how notions of the individual and population are evoked in two ongoing HIV treatment as prevention (TasP) implementation studies in Swaziland. By contrasting policy discourses with lived kinship experiences of people living with HIV, we seek to understand how TasP unfolds in the Swazi context. Data collection consisted of eight focus group discussions with people living with HIV who were members of support groups to examine their perspectives about TasP. In addition, 18 key informant inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 23 publications
1
16
0
Order By: Relevance
“…This boost was deemed necessary when PLHIV had a low CD4 count and/or were seriously ill. Reinfection is commonly understood as PLHIV preventing themselves from being infected with a different strain of HIV by abstaining from sex, consistently using condoms, or by having sex with the same long-term partner. Studies in Kenya 6 and Swaziland 7 also documented the latter concerns about reinfection among health workers and PLHIV. Zambian HIV specialists in one community said they discouraged PLHIV having multiple sexual partners partly because of the risk of reinfection.…”
Section: Methodsmentioning
confidence: 95%
See 1 more Smart Citation
“…This boost was deemed necessary when PLHIV had a low CD4 count and/or were seriously ill. Reinfection is commonly understood as PLHIV preventing themselves from being infected with a different strain of HIV by abstaining from sex, consistently using condoms, or by having sex with the same long-term partner. Studies in Kenya 6 and Swaziland 7 also documented the latter concerns about reinfection among health workers and PLHIV. Zambian HIV specialists in one community said they discouraged PLHIV having multiple sexual partners partly because of the risk of reinfection.…”
Section: Methodsmentioning
confidence: 95%
“…Resistance to the term was expressed by national policy makers and study implementers in Swaziland, partly on the basis of clarity and given that they were already moving toward offering this as the best standard of care. 7 …”
Section: Methodsmentioning
confidence: 99%
“…The average follow-up refers to the average time a study participant was observed in the context of the trial. strategies by the general population [29,[53][54][55][56][57][58][59][60][61][62][63][64][65][66][67][68][69]. Overall, the analysis of the various themes addressed within these five trials will contribute to understanding the impact of UTT strategies in various contexts as well as inform the generalization of such a strategy to new contexts.…”
Section: Trial Intervention Packagesmentioning
confidence: 97%
“…They might also work in the other direction to bring knowledge gained through long-term, grounded engagement with everyday life to spaces of global expertise so as to improve health experts' practices of design and dissemination. They might also do both (Vernooij et al 2016;Manderson 1998;Hardin 2018).…”
Section: Working In-betweenmentioning
confidence: 99%